E-036 The THERAPY Trial: a prospective, randomized, concurrent controlled trial to assess safety and effectiveness of the Penumbra System® as adjunctive treatment to IV rtPA in acute ischemic stroke. (4th July 2012) - Mocco, J; Zaidat, S; Khatri, P
Abstract : Introduction/purpose: The recognition that IV rtPA treatment has limitations in the revascularization of large vessel occlusions led to the development of intra-arterial (IA) mechanical thrombectomy devices for acute stroke intervention. Because it takes time for imaging to confirm a persistent large vessel occlusion after IV lytic treatment, it would be beneficial to identify a cohort a priori among IV rtPA-eligible patients who could benefit from IA mechanical intervention as an adjunctive treatment. In a recent paper, Riedel et al (Stroke 2011;42 :1775) suggested that patients with a clot length of at least 8 mm are likely to be refractory to IV rtPA and therefore good candidates for combined IV/IA therapies. The purpose of the THERAPY Trial is to assess the safety and effectiveness of the Penumbra System® as an adjunctive treatment to IV rtPA in a stroke cohort who is likely to be refractory to the lytic due to a large vessel occlusion and an extensive clot length of 8 mm or longer. Materials and Methods: The THERAPY Trial is a prospective, multicenter, randomized, concurrent controlled study (NCT01429350 ) with a primary aim to assess the safety and effectiveness of a mechanical thrombectomy device, the Penumbra System, as IA adjunctive treatment to IV rtPA in patients with acute ischemic stroke from large vessel occlusion and extensive clot burden in the anterior circulation. Patients from 18 to 85 years of age presenting with symptoms of acute ischemic stroke with an NIHSS score of >8 or aphasic who have evidence of a clot length ≥8 mm in the anterior circulation will be randomly assigned to either IV rtPA therapy alone (0.9 mg/kg to a maximum of 90 mg) or a combined IV rtPA therapy (0.9 mg/kg to a maximum of 90 mg) and IA adjunctive treatment with the Penumbra System. Each treated patient will be followed and assessed for effectiveness and safety for 3 months after randomization. Females who are pregnant, pre-morbid mRS score >1 and CT evidence of extensive infarction are excluded. The primary endpoints are good functional outcome at 90 days as defined by an mRS score of 0–2 and incidence of serious adverse events. Secondary endpoints are good neurological outcome at discharge and incidence of intracranial hemorrhage as adjudicated by a Core Laboratory. An independent Clinical Event Committee/Data Safety Monitoring Board will adjudicate safety events and monitor safety for the trial. Results: Nearly 40 centers have committed to THERAPY and, of those, 14 have already received IRB approval. Patient recruitment has begun, and enrolment is expected soon. To date, five centers are screening patients. Conclusion: Results from the THERAPY trial in 3 to 4 years would help expand our understanding of the role of IA mechanical thrombectomy as adjunctive therapy to IV rtPA treatment to improve clinical outcome, rather than simply for thrombus removal as an alternative to lytic therapy. With completion of randomized controlled trials such as THERAPY, IMS III (NCT00359424 ), and MR Rescue (NCT00389467 ), the management of acute ischemic stroke continues to evolve. Competing interests: J Mocco: Lazarus Effect, Edge Therapeutics, Nfocus, Concentric. Blockade Medical. S Zaidat: Penumbra, Codman, EV3, Microvention. P Khatri: IMS III Trial Exec Committee, NeuroNEXT PI, THERAPY Trial Neurology PI. Genentech.